2009
DOI: 10.1002/jso.21367
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of endoscopic thyroidectomy versus conventional open thyroidectomy in papillary thyroid microcarcinoma (PTMC) patients

Abstract: Background: The aim of this study was to evaluate and compare the early surgical outcomes of endoscopic and conventional open thyroidectomies in patients with papillary thyroid microcarcinoma (PTMC). Methods: Between September 2005 and December 2007, 499 patients with PTMC were enrolled. 275 patients underwent gasless endoscopic thyroidectomy via the axillary route (endo group), and 224 patients underwent conventional open thyroidectomy (open group). We analyzed the patient's clinico-pathologic characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
73
3

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(80 citation statements)
references
References 17 publications
(31 reference statements)
4
73
3
Order By: Relevance
“…The surgical techniques for conventional open and robotic thyroidectomy with our approach have been described in detail elsewhere, so a detailed description of the technique is therefore beyond the scope of this report [7,[12][13][14][15].…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The surgical techniques for conventional open and robotic thyroidectomy with our approach have been described in detail elsewhere, so a detailed description of the technique is therefore beyond the scope of this report [7,[12][13][14][15].…”
Section: Surgical Techniquementioning
confidence: 99%
“…Endoscopic thyroidectomy has several advantages over conventional thyroidectomy [4][5][6][7][8]. However, endoscopic thyroidectomy is a difficult technique for surgeons because of difficulties with adequate visualization and precise manipulation of the surgical field.…”
mentioning
confidence: 99%
“…The robot and endoscopy techniques and trocar arrangement have been described in detail elsewhere. 4,[6][7][8][9][14][15][16] Briefly, the patient was positioned in a supine position on a small shoulder roll. The ipsilateral arm was placed on an arm board and extended cephalad to expose the axilla.…”
Section: Operation Proceduresmentioning
confidence: 99%
“…[1][2][3][4][5] However, endoscopic thyroidectomy is a technically challenging procedure and has not been universally adopted. Two reasons for this may be that the 2-dimensional visual representation and nonflexible endoscopic instruments can make it difficult to adequately visualize the surgical field and to manipulate instruments.…”
mentioning
confidence: 99%
“…Figure 3 shows the endoscopic view of transaxillary thyroidectomy. On the other hand, some studies suggested that the trans-axillary approach might be associated with a higher rate of transient hypocalcemia and transient RLN palsy [36,37]. In a patient with a low-risk papillary thyroid microcarcinoma, Jeong et al reported that trans-axillary thyroidectomy with prophylactic central neck dissection was feasible.…”
Section: Extra-cervical/indirect Approachesmentioning
confidence: 99%